Deep trouble (London : Egmont, 2012)
When Mandy Flood and Norman Price go in search of buried treasure, it's not long before they find themselves in deep trouble. Fireman Sam and the Mountain Rescue crew face their most difficult rescue yet!
"Based on an original idea by D Gingell, D Jones and characters created by R.J.M. Lee."
Keywords: Children's stories